Kegiatan Pengabdian melalui Pelatihan Media Pembelajaran Interaktif bagi Guru MGMP IPA Kota Pekanbaru - Fauza, Naila; Azizahwati, Azizahwati; Azhar, Azhar; Andriani, Riza; Ratnawati, Sri Agustina; Dipuja, Diah Anugrah; Dahnuss, Dodi; Zahara, Alya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Education plays an important role in the advancement of science and technology in society. However, many teachers still face obstacles in utilizing mobile devices as interactive learning media, particularly in terms of understanding how to use the media and developing operational skills. This condition limits the variety of learning activities that can be presented in the classroom and reduces the optimal use of technology. This community service program was carried out through training involving 80 teachers from the MGMP IPA Pekanbaru City, focusing on the planning, implementation, and assessment of interactive media–based learning. The training was designed to provide teachers with hands-on experience in operating devices, becoming familiar with essential features, and integrating them into the teaching and learning process. This activity is expected to improve teachers’ understanding and skills in utilizing educational technology, thereby enabling them to be more proficient in using interactive media in the classroom. Consequently, teachers will be better prepared to face the challenges of technological development and contribute to improving the quality of education in schools.